1996
DOI: 10.1007/bf00179951
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography of the human nasal muscles

Abstract: Electromyographic (EMG) activity of six nasal muscles was monitored in 17 male volunteers without nasal complaints. Surface electrodes were placed on the nasal skin in such a way that they selectively recorded the activity of these muscles. Recordings were made under different breathing conditions and during voluntary nasal movements. Inspiratory EMG activity was observed during nasal and oral breathing in one or more of the following muscles: dilator naris, nasalis muscle (alar and transverse parts) and apici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…14 The nasalis muscle functions as an accessory respiratory muscle, helping to prevent collapse of the nasal pathway during inspiration; it is also involved in facial expressions. 4 Preliminary observations have shown that the nasalis muscle can be activated by inhaling forcefully or widening the nostrils, as if smelling something distasteful, but it seems to be difficult to sustain this activity for any length of time. But even if the nasalis muscle were to prove unsuitable to use in testing for an increment, this would not be an important drawback, as an increment in LEMS can be demonstrated well in small hand muscles.…”
Section: Discussionmentioning
confidence: 98%
“…14 The nasalis muscle functions as an accessory respiratory muscle, helping to prevent collapse of the nasal pathway during inspiration; it is also involved in facial expressions. 4 Preliminary observations have shown that the nasalis muscle can be activated by inhaling forcefully or widening the nostrils, as if smelling something distasteful, but it seems to be difficult to sustain this activity for any length of time. But even if the nasalis muscle were to prove unsuitable to use in testing for an increment, this would not be an important drawback, as an increment in LEMS can be demonstrated well in small hand muscles.…”
Section: Discussionmentioning
confidence: 98%
“…Patency of the NVA is critical for nasal function [3]. Minor alterations in air flow create difficulty in breathing and nasal obstruction [7,10].…”
mentioning
confidence: 99%
“…The role of muscular activity in the nasal airway has been demonstrated previously by various methods [4,26]. Kienstra et al [26] reported that RMM can be used to determine the function of the nasal muscles.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the SMAS allows for distribution of the forces that result from contractions of the multiple muscles connecting the nasal muscles (and their fascia) to each other and balances their movements. This complex structure comprising the SMAS, nasal muscles, and ligaments allows for the control of phonation, respiration, and facial expressions [4]. The SMAS lies superior to the galea aponeurotica at the rhinion level and inferior to the procerus muscle fascia, moves caudally at the nasal dorsum, and joins with interdomal cross-fibers.…”
Section: Introductionmentioning
confidence: 99%